PENGARUH INDEPENDENSI, TEKANAN ANGGARAN WAKTU, RISIKO AUDIT DAN GENDER TERHADAP KUALITAS AUDIT (Studi Kasus Pada 8 Kantor Akuntan Publik Wilayah Semarang) - Ririn Rizky Ayu Wardani, 15.05.52.0326; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of independence, time budget pressure, audit risk, and gender on audit quality. This research was conducted at the Public Accounting Firm in the Semarang Region. The population in this study were all auditors who were in the Public Accounting Office in the Semarang area. Sampling using the convenience sampling method. The primary data collection method used is the questionnaire method with data analysis using multiple linear regression models. The results showed that independence had a significant positive effect on audit quality, while the time budget pressure, audit risk and gender did not significantly influence audit quality.